2022
DOI: 10.21744/ijbem.v5n1.1867
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intention to buy healthy food

Abstract: Research on the intention to buy healthy food products is interesting to study because many studies show mixed results. The purpose of this study was to determine the effect of health awareness factors, attitude factors, environmental awareness, lifestyle, and knowledge on purchase intentions of healthy food products with case observation settings in Solo City involving 100 respondents. The results of the analysis show that the four variables of health awareness, attitude, environmental awareness, and lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Checking for convergent validity may include looking at both the external loading value and the Average Variance Extracted (AVE) value. The AVE value must be greater than 0.5 to prove convergent validity (Kusdiyanto, et al,2022).…”
Section: Resultsmentioning
confidence: 99%
“…Checking for convergent validity may include looking at both the external loading value and the Average Variance Extracted (AVE) value. The AVE value must be greater than 0.5 to prove convergent validity (Kusdiyanto, et al,2022).…”
Section: Resultsmentioning
confidence: 99%
“…The underlying argument is that the samples have understood halal products. In addition, it is hoped that the selection of the millennial generation sample will support access to information search about halal products (Irawati, et al, 2023;Kusdiyanto, et al, 2022;Hashim, et al, 2022).…”
Section: Research Methods Samples and Analysis Toolsmentioning
confidence: 99%
“…The validity test results showed that all indicators were grouped according to the specified variables, confirming the validity of all these indicators. Validity testing is essential to know the validity measurement of all indicators explaining a variable in research (Saputro & Achmad, 2015;Irawati, et al, 2023;Kusdiyanto, et al, 2022). The validity test results are shown in Table 3 as follows: The reliability test results revealed that the instruments used in research to obtain respondent information could show the truth.…”
Section: Validity and Reliability Testmentioning
confidence: 99%
See 2 more Smart Citations